Electrolytes, Zinc and Vitamin D3 in COVID-19 Patients with Cardiovascular Complications - Ali Abdel-Moneim Mohammed-Hussain AlKhuzaie; Enas Abdul Kareem Jabbar; Bushra Jabbar Albadry (Вопросы вирусологии, 2024)
Introduction. COVID-19 is strongly linked to cardiovascular disease, with direct myocardial injury and systemic inflammation as common mechanisms. Pre-existing or infection-induced cardiovascular disease worsens the outcomes for COVID-19 patients.